2007
DOI: 10.1152/ajpendo.00295.2007
|View full text |Cite
|
Sign up to set email alerts
|

Increased TNFα and CCAAT/enhancer-binding protein homologous protein with aging predispose preadipocytes to resist adipogenesis

Abstract: Fat depot sizes peak in middle age but decrease by advanced old age. This phenomenon is associated with ectopic fat deposition, decreased adipocyte size, impaired differentiation of preadipocytes into fat cells, decreased adipogenic transcription factor expression, and increased fat tissue inflammatory cytokine generation. To define the mechanisms contributing to impaired adipogenesis with aging, we examined the release of TNF␣, which inhibits adipogenesis, and the expression of CCAAT/enhancer-binding protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 70 publications
(97 reference statements)
3
54
0
Order By: Relevance
“…In fact, in some studies, s.c. obesity is even protective against the effects of visceral obesity (3). Several factors have been suggested to contribute to these differences: first, anatomical differences between visceral and s.c. fat, and especially the fact that visceral fat drains directly into the portal vein, exposing the liver to higher levels of free fatty acids, adipokines, and cytokines, which can lead to insulin resistance (22); second, obesity is associated with inflammation and the infiltration of activated macrophages into fat, and these occur to a greater extent in visceral fat compared with s.c. fat (23); and finally, a number of studies indicate intrinsic differences in gene expression between adipocytes from different fat depots, which might lead to different biological and physiological function (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in some studies, s.c. obesity is even protective against the effects of visceral obesity (3). Several factors have been suggested to contribute to these differences: first, anatomical differences between visceral and s.c. fat, and especially the fact that visceral fat drains directly into the portal vein, exposing the liver to higher levels of free fatty acids, adipokines, and cytokines, which can lead to insulin resistance (22); second, obesity is associated with inflammation and the infiltration of activated macrophages into fat, and these occur to a greater extent in visceral fat compared with s.c. fat (23); and finally, a number of studies indicate intrinsic differences in gene expression between adipocytes from different fat depots, which might lead to different biological and physiological function (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…These clear differences between s.c. and visceral fat suggest that, in addition to their anatomical location, these fat depots have intrinsic differences at the cellular level. These studies have demonstrated major functional and gene expression differences between s.c. and visceral fat (6,7). Both isolated adipocytes and the stromovascular fraction containing preadipocytes show cell autonomous differences in the expression of developmental patterning genes between s.c. and visceral depots, suggesting different developmental origins for these fat depots (8).…”
mentioning
confidence: 99%
“…5 Actually, RNase L À/À mice possess a higher number of smaller adipocytes than WT mice ( Figure 8A), that is characteristic of hyperplasia. 31 This number of adipocytes increases with aging, as we observed an adipose tissue expansion in aged RNase L À/À mice.…”
Section: Discussionmentioning
confidence: 97%
“…At present, it is known that CHOP10 is more expressed in old individuals preadipocytes than from young ones. 5 Change in adipogenesis process is due to the incapacity of preadipocytes to express appropriate levels of key adipogenic regulators: CHOP10, C/EBPa and PPARg. 4,32 We assume that overexpression of CHOP10 in RNase L À/À mice added to the physiological overexpression of CHOP10 in old age would lead to even higher levels of CHOP10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation